Electrode-particle impacts: a users guide - Sokolov, S; Eloul, S; Kätelhön, E; Batchelor-McAuley, C; Compton, R (Royal Society of Chemistry, 2016)
We present a comprehensive guide to nano-impact experiments, in which we introduce newcomers to this rapidly-developing field of research. Central questions are answered regarding required experimental set-ups, categories of materials that can be detected, and the theoretical frameworks enabling the analysis of experimental data. Commonly-encountered issues are considered and presented alongside methods for their solutions.